EFEKTIVITAS TERAPI PERILAKU KOGNITIF UNTUK MENGURANGI KECEMASAN BERBICARA DI MUKA UMUM - Purnamaningsih, Esti Hayu; Utami, Muhana Sofiati (Faculty of Psychology, Universitas Gadjah Mada, 1998)
There were facts t i i mutij)t students have no ability in, and feel anxious, when they have to speak in public (i.e. seminar, discussion, etc.j. The purpose ofthe research was to investigate the effectiveness of cognitive behavior therapy that given to minimize anxiety in public speaking. The subjects were studetlts ofthe Faculty of Psychology, Wangsa Manggala University in Yogvakarta, u ho had atxiety in public speaking and volunteered to participate in the research. There were 20 student, ten were in the experimental group given the treatment of cognitive behavior therapy. The other ten were in the control group, would be given the therapy after the research had been completed. The subject's an iet4, before and after the treatment were measured The experiment was conducted by two therapist in five sessions, each sessions was held in 90 minutes. The process of the experiment was observed, and recorded with audio tape recorder. The data was analized quantitatively and qualitatively. The quantitative data was analized with one-way Anove mixed I factor, and the data from the observational record and self report from the subjects were analized qualitatively. The results showed that there was a decrease in public-speaking anxiety of the experimental group. The mean before therapy was 104.300 and after therapy was 85.300. In the control group that had not been treated, there was an increase in anxiety between are pretest and the posttest. The pretest mean was 105.700 and the posttest was 112.800. The qualitative data analysis showed that The Cognitive Behavior Therapy had been usefull to reduce anxiety in public speaking